Hate parties: limits on the freedom of extreme political parties - Szigeti, T (2013)
This thesis deals with the question of dissolution of extremist political parties at the European Court of Human Rights (ECtHR). Liberal democracies are characterised by freedom and pluralism. On the one hand, one could say that democracy is precisely about tolerating all opinions in politics; on the other, one could also say that democracy should only tolerate political parties to the extent that they do not jeopardise its own foundations. The ECtHR has to face the new paradigm in extremism that resulted in intolerant fringe parties replacing totalitarian parties. While the Court delivered a substantial number of judgments in party dissolution cases, yet it remains unknown what the oft-repeated high protection for freedom of association will mean in difficult dissolution cases in the future. The present study rethinks the ways the Court should interpret party dissolution cases to meet the challenge of new extremism. First, the thesis draws attention to the various aspects of a party’s activities that the Court should observe in dissolution cases. Second, the thesis further argues that the Court should revitalise the definition stage of adjudication instead of uniquely relying on proportionality and balancing. Any dissolution case should start from defining what political parties are in a normative sense. Third, balancing understood as principled reasoning, should follow only after the definition. Drawing on the jurisprudence on articles 10, the thesis tries to rethink the balancing process in party dissolution cases of new extremist parties. It argues that because the legitimacy of the democratic government depends in part on the respect for political rights, chief amongst them the freedom of association, only compelling reasons and extraordinary circumstances may justify party dissolution. Finally, the thesis will outline such extra reasons with the help of other jurisdictions.